THE ESSENCE OF CLASSICAL AND MODERN CONCEPTS: GENERAL CHARACTERISTICS - Сутула, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The essence and the origin of classical and modern geopolitical concepts are considered. The meaning of «geopolitics» is explored, geopolitical approaches are presented and a personal vision of this definition is offered. The content is analyzed; the correlation of classical and modern concepts of geopolitics is systematized. It is argued that the key problem of geopolitics is the confrontation between the telurocratic and talasocratic principles and their influence on the development and formation of the state.